2022
DOI: 10.1021/acsami.2c12445
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Self-Healing Gel Electrolyte Based on Deep Eutectic Solvents for Solid-State Lithium Batteries

Abstract: A deep eutectic solvent (DES) is a promising electrolyte choice for lithium metal batteries. However, the DES liquid electrolyte causes safety concerns and side reactions with the lithium anode. Therefore, it is necessary to solidify the DES-based electrolyte and enhance its electrochemical stability. Herein, we present a novel DES-based rapid self-healing gel electrolyte, which is able to self-smooth its surface cracks in only 30 min. The electrolyte exhibits noncombustibility (SET = 4 s g–1), high ionic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Non-flammable alternatives, such as deep eutectic solvents and ionic liquid-based electrolytes, have been explored to mitigate this hazard. However, polymer electrolytes, while non-flammable, often suffer from deformation and breakage during the charge-discharge process, leading to interface contact issues [154][155][156]. Addressing this challenge, self-healing electrolytes have emerged as a promising solution, capable of inhibiting such problems and improving electrochemical performance while reducing degradation.…”
Section: Self-healing Gelsmentioning
confidence: 99%
“…Non-flammable alternatives, such as deep eutectic solvents and ionic liquid-based electrolytes, have been explored to mitigate this hazard. However, polymer electrolytes, while non-flammable, often suffer from deformation and breakage during the charge-discharge process, leading to interface contact issues [154][155][156]. Addressing this challenge, self-healing electrolytes have emerged as a promising solution, capable of inhibiting such problems and improving electrochemical performance while reducing degradation.…”
Section: Self-healing Gelsmentioning
confidence: 99%
“…While the first HBD used for the realization of DES-based electrolytes is acetamide [170] , its use has quickly become obsolete due to the instability of N-H bonds with lithium metal anodes. As a result, NMA is the main choice as the HBD to realize DES-based electrolytes for LMBs [171][172][173][174][175][176] .…”
Section: Deep Eutectic Solventsmentioning
confidence: 99%
“…Furthermore, Wang et al reported the use of an eutectogel based on Li[TFSI]:NMA (1:4 in mol) in a PEO matrix, which also contains metal-organic-framework (MOF) UiO66-NH 2 [175] . The reactivity of NMA with lithium metal was reduced due to the interaction between the NH 2 group of the MOF and the C=O group of NMA.…”
Section: Deep Eutectic Solventsmentioning
confidence: 99%
“…Numerous options of HBAs and HBDs as well as different mixture compositions provide great possibilities to search ES with desirable properties. Holding such great potential for practical application, ESs are widely expected as promising process media for various chemical processes, such as liquid–liquid extraction, gas capture, catalysis, electrodeposition, etc. Identically, the challenge to realize a technically and economically advantageous ES-based process is the selection of a suitable ES. Therefore, CAMD methods have also been attempted to guide the rational screening and design of ESs by several researchers.…”
Section: Representative Applications Of Computer-aided Il Screening A...mentioning
confidence: 99%